Defects of diamond crystal structure as an indicator of crystallogenesis - Evgeny A. Vasilev (Journal of Mining Institute, 2021)
Based on the study of a representative collections of diamonds from diamondiferous formations of the Urals and deposits of the Arkhangelsk and Yakutian diamond provinces, we established patterns of zonal and sectoral distribution of crystal structure defects in crystals of different morphological types, identified the specifics of crystals formed at different stages of crystallogenesis and performed a comprehensive analysis of constitutional and population diversity of diamonds in different formations. We identified three stages in the crystallogenesis cycle, which correspond to normal and tangential mechanisms of growth and the stage of changing crystal habit shape. At the stage of changing crystal habit shape, insufficient carbon supersaturation obstructs normal growth mechanism, and the facets develop from existing surfaces. Due to the absent stage of growth layer nucleation, formation of new {111} surfaces occurs much faster compared to tangential growth mechanism. This effect allows to explain the absence of cuboids with highly transformed nitrogen defects at the A-B1 stage: they have all been refaceted by a regenerative mechanism. Based on the revealed patterns, a model of diamond crystallogenesis was developed, which takes into account the regularities of growth evolution, thermal history and morphological diversity of the crystals. The model implies the possibility of a multiply repetitive crystallization cycle and the existence of an intermediate chamber; it allows to explain the sequence of changes in morphology and defect-impurity composition of crystals, as well as a combination of constitutional and population diversity of diamonds from different geological formations.